A review of tropical forestry and agroforestry problem areas and policy research needs and the planned response of the CGIAR system - Spears, J.; Oram, Peter A.; Byron, R.N.; Scherr, Sara J.; Izac, A.M.N. (1995)
The idea of holding an international workshop on priorities for forestry/agroforestry policy research stemmed from discussions among a number of concerned scientists, some of whom (Hans Gregersen, Peter Oram, John Spears) had been involved in TAC, CGIAR, IUFRO, and other discussions on international research needs for the forestry sector, the potential role of the CGIAR and what IFPRI's contribution might be within this larger framework. IUFRO and USAID offered to fund such a workshop, and it was agreed to hold it in Washington with IFPRI as the operational focus and host. A key recommendation of this workshop was to follow up with similar workshops in each of the major geographical regions where tropical forestry is important, and IFPRI was asked to pursue this. The aim was to delineate more specifically the problems and priority areas for research, and to identify those researchable issues common to several countries, the results of which would have broad applicability; as well as where international action might be needed when problems transcended national boundaries or presented difficult methodological challenges. IFPRI agreed to take on this task, and Peter Oram, who had the primary responsibility for organizing the international workshop, was designated by IFPRI as task manager. John Spears and Hans Gregersen played an important advisory role, and John participated in the Asian and African workshops. Sara Scherr, who had been present at the international workshop and who joined IFPRI in 1991, participated in the Asian, African, and Latin American Workshops; Manuel Paveri of FAO also participated in the Asian, African, and Latin American workshops and provided a valuable link with FAO's Forest Policy Program. Marc de Montalambert, Director, Forest Policy and Planning Division in FAO, also attended the International and Asian workshops, and FAO was the lead agency managing the joint FAO/IFPRI Asian workshop in Bangkok. Ronnie de Camino was the main partner in the Latin American initiative. Peter Oram played the leading role in raising funds, organising all of the workshops jointly with IFPRI's partners in Asia (FAO), Africa (ICRAF), and Latin America (IICA), running the three regional meetings, and writing the reports. He, John Spears, Sara Scherr and Ann-Marie Izac participated in the Bogor workshop and contributed to the draft report. Neil Byron convened and organised this last meeting and also attended the Washington and Asian workshops.